REVIEW OF SOLAR AIR HEATERS EMBEDDED WITH PHASE-CHANGE MATERIALS (PCM) FOR BETTER PERFORMANCES - VISARION-CĂTĂLIN IFRIM; TEODOR POP; CIPRIAN BEJENAR (Journal of Engineering Studies and Research)
The technology of solar air heating systems is one of the branches that is of great importance in capturing and capitalizing on solar energy. This paper presents a summary of the literature on solar air heating systems embedded with materials that have the ability to retain thermal energy, during periods of maximum intensity of solar radiation and its release, when solar energy is reduced or missing for a period of time. It presents the designed and carried out systems by different researchers and the thermal performances obtained in the period of 2017-2021.